Modular Nanotransporters for Nuclear-Targeted Delivery of Auger Electron Emitters - Sobolev, Alexander S. (Frontiers in Pharmacology, 2018)
This review describes artificial modular nanotransporters (MNTs) delivering their cargos into target cells and then into the nuclei – the most vulnerable cell compartment for most anticancer agents and especially for radionuclides emitting short-range particles. The MNT strategy uses natural subcellular transport processes inherent in practically all cells including cancer cells. The MNTs use these processes just as a passenger who purchased tickets for a multiple-transfer trip making use of different kinds of public transport to reach the desired destination. The MNTs are fusion polypeptides consisting of several parts, replaceable modules, accomplishing binding to a specific receptor on the cell and subsequent internalization, endosomal escape and transport into the cell nucleus. Radionuclides emitting short-range particles, like Auger electron emitters, acquire cell specificity and significantly higher cytotoxicity both in vitro and in vivo when delivered by the MNTs into the nuclei of cancer cells. MNT modules are interchangeable, allowing replacement of receptor recognition modules, which permits their use for different types of cancer cells and, as a cocktail of several MNTs, for targeting several tumor-specific molecules for personalized medicine.